(untitled) (Revista Música, 2018)
The motet a 5, Jerusalem surge (‘Liber octavus ecclasiasticarum’, Tylman Susato, Antwerp, 1553) by Jacobus Clemens non Papa, is based on the verse and responsory of one of the antiphons sung on the second Sunday of Advent. In this study, we propose the analysis considering two complementary approaches: (1) the exegetical reading by the synchronic analysis and (2) the analysis of the musical structures revealed by German primary sources. A detailed examination of the possible relationships between such aspects contributes to an approach which contemplates music as a means by which the text evokes a particular mode of signification.